Genetic evolution of nevus of Ota reveals clonal heterogeneity acquiring BAP1 and TP53 mutations. (March 2016) - Vivancos, Ana; Caratú, Ginevra; Matito, Judit; Muñoz, Eva; Ferrer, Berta; Hernández‐Losa, Javier; Bodet, Domingo; Pérez‐Alea, Mileidys; Cortés, Javier; Garcia‐Patos, Vicente; Recio, Juan A.
Summary: Melanoma presents molecular alterations based on its anatomical location and exposure to environmental factors. Due to its intrinsic genetic heterogeneity, a simple snapshot of a tumor's genetic alterations does not reflect the tumor clonal complexity or specific gene–gene cooperation. Here, we studied the genetic alterations and clonal evolution of a unique patient with a Nevus of Ota that developed into a recurring uveal‐like dermal melanoma. The Nevus of Ota and ulterior lesions contained GNAQ mutations were c‐KIT positive, and tumors showed an increased RAS pathway activity during progression. Whole‐exome sequencing of these lesions revealed the acquisition of BAP1 and TP53 mutations during tumor evolution, thereby unmasking clonal heterogeneity and allowing the identification of cooperating genes within the same tumor. Our results highlight the importance of studying tumor genetic evolution to identify cooperating mechanisms and delineate effective therapies.